How Self Control and Situational Pressure Influence the Tendency to Receive Gratification: An Experimental Study - Ariyanto, Dodik; Maulana Firdaus, Gilang; Mediatrix Ratna Sari, Maria; Aryista Dewi, Ayu; Gilang Jhuniantara, I Made (International Journal of Criminology and Sociology, 2022)
This study aimed to produce empirical evidence on tendency differences to accept gratuities between individuals with a high level of self-control and a low level of self-control, the conditions are the presence or absence of situational pressure. The method used is an experiment with a 2x2 factorial design. A total of 136 officers and staff in the Directorate General of State Bali region become research participants. The data were processed with statistical parametric, two-way ANOVA. The results showed that individuals with high levels of self-control have a lower tendency to accept gratuities than participants with lower levels of self-control. However, this study did not obtain empirical evidence indicating situational pressures experienced by the individual can affect the tendency to accept gratuities. Interaction hypothesis testing showed that the interaction between the individual levels of self-control and situational pressures experienced affects the tendency to accept gratuities.